RETRACTED: Improvement of wheat cultivation technology with Increased yield and product quality - Milyutkin Vladimir; Kirov Yri; Rudoy Dmitry; Olshevskaya Anastasiya; Odabashyan Mary; Prutskov Aleksey; Vershinina Anna; Sarkisian Dzhuletta (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001